Major Livestock Routes in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2025)
A map of major livestock routes in Ethiopia. The mapping was undertaken by government representatives. Developed in partnership with the Government of Kenya and the IGAD Center for Pastoral Areas and Livestock Development.